Pengaruh Stres Kerja terhadap Kepuasan Kerja dengan Motivasi Kerja Sebagai Variabel Mediasi pada Karyawan Bebek Uma Sari Resto Singapadu, Gianyar - Ni Made Galih Sekar Wangi; I Gusti Ayu Dewi Adnyani (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Job satisfaction comes because someone feels a good feeling from a job evaluation and also the characteristics related to job satisfaction itself. Thus the company must know what things will affect the job satisfaction of its employees. This study aims to determine job stress on job satisfaction with work motivation as a mediating variable in employees of Bebek Uma Sari Resto, Singapadu Gianyar. This research was conducted at Bebek Uma Sari Resto, Singapadu Gianyar with a total sample of 50 employees. The method of determining the sample in this study is saturated sampling method. Data collection is done through observation, interviews, and questionnaires. Instrument test used is validity test and reliability test. The data analysis technique in this study uses path analysis techniques, classical assumption tests, and sobel tests. Based on the results of the analysis, this study shows that job stress has a negative and significant effect on job satisfaction in employees of Bebek Uma Sari Resto, Singapadu Gianyar. Job stress has a negative and significant effect on work motivation in employees of Bebek Uma Sari Resto, Singapadu Gianyar. Work motivation has a positive and significant effect on job satisfaction in employees of Bebek Uma Sari Resto, Singapadu Gianyar, and work motivation is a mediating variable between work stress and job satisfaction in employees of Bebek Uma Sari Resto.